2011
DOI: 10.3389/fncel.2011.00029
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment decreases GABAergic inhibition and improves cognitive abilities, synaptic plasticity, and visual functions in a mouse model of Down syndrome

Abstract: Down syndrome (DS) is the most common genetic disorder associated with mental retardation. It has been repeatedly shown that Ts65Dn mice, the prime animal model for DS, have severe cognitive and neural plasticity defects due to excessive inhibition. We report that increasing sensory-motor stimulation in adulthood through environmental enrichment (EE) reduces brain inhibition levels and promotes recovery of spatial memory abilities, hippocampal synaptic plasticity, and visual functions in adult Ts65Dn mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…Our data are congruent with the results obtained by Begenisic et al [6] in a Ts65Dn murine model of DS, where they demonstrated that EE was able to favor recovery from cognitive impairment, synaptic plasticity failure, and visual deficits.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Our data are congruent with the results obtained by Begenisic et al [6] in a Ts65Dn murine model of DS, where they demonstrated that EE was able to favor recovery from cognitive impairment, synaptic plasticity failure, and visual deficits.…”
Section: Discussionsupporting
confidence: 96%
“…The modulation of expression of crucial molecular mediators, such as IGF-1 and BDNF, has been identified as a key mechanism mediating EE effects and also confirmed in human conditions. Moreover, it has been recently reported that in a mouse model of DS, Ts65Dn line, increased sensory-motor stimulation in adulthood through EE reduces brain inhibition levels and promotes recovery of some abilities, including visual functions [6]. EE in mice by sensory-motor stimulation is similar to the technique of infant massage (IM) in humans.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have observed that the levels of GAD65 (another isoform of the enzyme responsible of GABA synthesis) remain unaltered in the hippocampus [22,27], but in those studies the authors found a higher degree of colocalization of synaptophysin and GAD65, suggesting a possible alteration in the proportion of excitatory and inhibitory contacts [22]. Additionally, other studies have observed and excess of GABA release in trisomic mice [53]. Other studies have observed also a higher sensitivity of inhibition, as a consequence of changes in GABA receptors and in potassium channels [27,54,55] therefore increasing the inhibition of the system.…”
Section: Neuropil Expressionmentioning
confidence: 87%
“…In particular, EE rescues spatial memory and dentate gyrus LTP as well as neuronal proliferation in Ts65Dn animals (Begenisic et al, 2011; Chakrabarti et al, 2011). Moreover, cortical LTP, anxiety behavior, motor coordination and spatial learning could be rescued in MECP2 null mice by EE (Kondo et al, 2008; Nag et al, 2009; Kerr et al, 2010; Lonetti et al, 2010) with an indication that the inhibitory GABAergic system could be preferentially responsible for the effect (Boggio et al, 2010; Lonetti et al, 2010).…”
Section: Gabaergic Therapies: Toward Innovation and Beyondmentioning
confidence: 99%